2017
DOI: 10.1111/cas.13297
|View full text |Cite
|
Sign up to set email alerts
|

RIN1 promotes renal cell carcinoma malignancy by activating EGFR signaling through Rab25

Abstract: We previously identified the important role of RIN1 expression in the prognosis of clear cell renal cell carcinoma (ccRCC). The role of RIN1 in ccRCC malignancy and underlying molecular mechanisms remain unclear. Here we report that ccRCC cells and tissues expressed more RIN1 than normal controls. Gain‐of‐function and loss‐of‐function studies demonstrated that RIN1 enhanced ccRCC cell growth, migration and invasion abilities in vitro and promoted tumor growth and metastasis in vivo. Mechanistic studies reveale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 42 publications
0
15
0
Order By: Relevance
“…In the present study, the potential target of miR-761 was predicted using bioinformatics analysis, and RIN1 (a Ras effector protein) was identified as a molecule of interest. Previous studies have shown that RIN1 promotes tumor progression in non-small cell lung cancer, bladder urothelial carcinoma, renal cell carcinoma, melanoma, gastric adenocarcinoma and hepatocellular cancer (1622). However, the mechanism of RIN1 in promoting tumor progression had not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the potential target of miR-761 was predicted using bioinformatics analysis, and RIN1 (a Ras effector protein) was identified as a molecule of interest. Previous studies have shown that RIN1 promotes tumor progression in non-small cell lung cancer, bladder urothelial carcinoma, renal cell carcinoma, melanoma, gastric adenocarcinoma and hepatocellular cancer (1622). However, the mechanism of RIN1 in promoting tumor progression had not been determined.…”
Section: Discussionmentioning
confidence: 99%
“…We predicted that RIN1 was one of the potential targets of miR-3619-5p using software Targetscan (http:// www.targetscan.org/vert_71/). RIN1 is associated with renal cell carcinoma aggressiveness (Feng et al, 2017). The potential miR-3619-5p binding site on RIN1 gene was located in the 3' untranslated region (3'UTR) (Fig.…”
Section: Mir-3619-5p Targets Rin1 To Regulate Rb Progressionmentioning
confidence: 99%
“…The expression of Ras and Rab interactor 1 (RIN1) expression increases and is related to poor prognosis in many tumors, including non-small cell lung cancer (Wang et al, 2012), melanoma (Fang et al, 2012), gastric adenocarcinoma (Yu et al, 2012) and renal cancer (Wei et al, 2015). It has been reported that RIN1 overexpression aggravated tumor cells through activating EGFR signaling (Feng et al, 2017). RIN1 is predicted to be one of the potential targets of miR-3619-5p, while miR-3619-5p was predicted to be one of LINC00202 targets.…”
Section: Introductionmentioning
confidence: 99%
“…Akt and Erk phosphorylation are increased when EGFR is activated in RCC (37,38). Previous studies have provided direct evidence that the EGFR signaling pathway is highly activated in RCC progression and EGFR expression is associated with prognosis in patients with clear cell RCC (38)(39)(40). Furthermore, inactivation of the EGFR signaling pathway inhibited RCC cell migration and invasion in vitro (41).…”
Section: Discussionmentioning
confidence: 99%